Analisis Yuridis Pidana Penjara dan Rehabilitasi terhadap Pecandu Narkotika Jenis Shabu (Studi Putusan Pengadilan Negeri Sei Rampah Nomor 9/Pid.Sus/2024/PN Srh) - Marfiansyah; Rachmat Hidayat (Albayan Journal of Islam and Muslim Societies, 2024)
This study analyzes the juridical aspects of imprisonment and rehabilitation for drug addicts, focusing on crystal methamphetamine (“shabu”) abuse as examined in the District Court of Sei Rampah Decision No. 9/Pid.Sus/2024/PN Srh. Using a normative juridical method with a statutory and case approach, this research explores how the principles of punishment and rehabilitation interact within Indonesia’s narcotics legal framework. The findings reveal that the court tends to impose imprisonment instead of rehabilitation, showing a preference for deterrence rather than recovery. Such a stance creates tension between the punitive and therapeutic aspects of criminal justice. The study argues that a restorative and therapeutic justice approach, emphasizing human rights and social reintegration, should be prioritized to realize a humane and balanced narcotics criminal policy in Indonesia.